Stock investment and excess returns: A critical review in the light of the efficient market hypothesis - Ying Qianwei; Tahir Yousaf; Qurat Ul Ain; Yasmeen Akhtar; Muhammad Shahid Rasheed (Journal of Risk and Financial Management, 2019)
The expansion of investment strategies and capital markets is altering the significance and empirical rationality of the Efficient Market Hypothesis. The vitality of capital markets is essential for efficiency research. The authors explore here the development and contemporary status of the efficient market hypothesis by emphasizing anomaly/excess returns. Investors often fail to get excess returns; however, thus far, market anomalies have been witnessed and stock prices have diverged from their intrinsic value. This paper presents an analysis of anomaly returns in the presence of the theory of the efficient market. Moreover, the market efficiency progression is reviewed and its present status is explored. Finally, the authors provide enough evidence of a data snooping issue, which violates and challenges the existing proof and creates room for replication studies in modern finance.
Keywords: 330; excess returns; efficient market hypothesis; data snooping; investment and capital markets